Vegetables, Heavy metals, FAAS, Kajian Cemaran Logam Berat Timbal (Pb), Kadmium (Cd), Dan Merkuri (Hg) Pada Sayuran Di Daerah Pertambangan Aceh Jaya Secara Spektrofotometri Serapan Atom. - Kurniaty , Rina; Adiyana, T.M. Dayan; Yusuf , Muhammad; Mahmudi , Mahmudi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Heavy metal contamination in vegetables poses a threat to humans, especially at predetermined thresholds. In this study, Pb, Cd, and Hg metals were analyzed using Flame - Atomic Absorption Spectrometry (F-AAS) and Vapor Generation Accesory - Atomic Absorption Spectrometry (VGA-AAS) methods at mining areas in Krueng Sabee Sub-District, Aceh Jaya District, Aceh Province. Method validation was conducted to obtain accurate heavy metal analysis results on the samples. The results showed that the highest Pb metal contamination was found in cassava leaf I sample with levels of 2.44 ± 1.33 mg/Kg and the lowest was found in spinach III sample with levels of 0.15 ± 0.07 mg/Kg. The high Pb content was also found in kale I and spinach I samples obtained in areas close to the mining area with levels of 1.07 ± 0.59 mg/Kg and 0.93 ± 0.50 mg/Kg, respectively. The highest Cd metal contamination content was found in kale II samples with levels of 0.11 ± 0.01 mg/Kg and the lowest Cd metal contamination with levels of 0.02 ± 0.01 mg/Kg was found in cassava leaf II samples. The highest Hg metal content of 0.58 ± 0.12 mg/Kg was found in cassava leaf I sample and the lowest level was 0.04 ± 0.02 mg/Kg owned by spinach III sample. Contamination of Hg metal in all vegetable samples showed levels that were above the established SNI 7387 (2009) quality standard of 0.03 mg/Kg. The quality standards for Pb and Cd metal contamination are 0.5 mg/Kg and 0.2 mg/Kg, respectively. This study shows the need for government monitoring of heavy metal contamination in agricultural areas near mining activities to ensure safe food consumption.